The impact of microscopic extrathyroidal extension on the clinical outcome of classic subtype papillary thyroid microcarcinoma: a multicenter study - Zuhur, Sayid Shafi; Aggul, Hunkar; Avci, Ugur; Erol, Selvinaz; Tuna, Mazhar Muslum; Uysal, Serhat; Elbuken, Gulsah (Springer, 2024)
Objectives Despite the presumed overdiagnosis of papillary thyroid microcarcinoma (PTMC) which has resulted in a new trend toward less-extensive surgery and a preference for active surveillance, the impact of microscopic extrathyroidal extension (mETE) on the clinical outcomes of PTMC is still controversial. This study assessed the impact of mETE on the clinical outcomes of patients with classic subtype PTMC. Methods The data of consecutive patients who underwent thyroidectomy and were histopathologically diagnosed as classic subtype PTMC were analyzed. Cox's proportional hazards model was used to assess the impact of contributing variables on persistent/recurrent disease. Disease-free survival was estimated using the Kaplan-Meier method. Results This study included 1013 patients (84% females), with a mean follow-up period of 62.5 +/- 35.3 months. Patients with mETE had a significantly higher rate of locoregional persistent/recurrent disease than patients without mETE (9.8% vs 2.1%, p < 0.001). The disease-free survival rate was significantly lower in patients with mETE than in those without (90.2% vs 97%, Log-Rank p < 0.001). Furthermore, mETE and neck lymph node involvement were independent predictors of persistent/recurrent disease in multivariate analysis (HR: 2.43, 95% CI:1.02-5.81, p = 0.043; HR: 4.38, 95% CI: 1.7-11.2, p = 0.002, respectively). Conclusions In patients with the classic subtype of PTMC, mETE is an independent predictor of persistent/recurrent disease and is associated with a lower DFS rate. However, neck lymph node involvement is the strongest predictor of persistent/recurrent disease. Therefore, PTMCs with mETE and neck lymph node involvement are at a higher risk of persistent/recurrent disease than individuals lacking both characteristics.
Keywords: Microscopic extrathyroidal extension; Papillary thyroid microcarcinoma; Disease-free survival; Recurrence